Performance Analysis of Lecturers of Computer Science Study, FMIPA, HKBP Nommensen University Pematangsiantar - Natasya Agustina Girsang; Nirma Sintina; Yosia Parapat; Mastiur Verawaty Silalahi; Masni Veronika Situmorang (Jurnal Ilmiah Multidisiplin Nusantara (JIMNU), 2026)
This study aims to assess the performance of lecturers in the Computer Science Study Program at HKBP Nommensen University Pematangsiantar from the perspective of students and identify areas that need improvement to enhance the academic quality of the study program. The study uses a quantitative approach through a survey. The researchers collected data using a five-point Likert scale questionnaire distributed to 103 students of the Computer Science Study Program who had attended lectures. The researchers analyzed five aspects: teaching readiness, teaching materials, teaching discipline, teaching evaluation, and lecturer personality. We analyzed the data using descriptive statistics, calculating the percentage of student responses for each aspect of the assessment. The results of the study show that the performance of lecturers in the Computer Science Study Program at HKBP Nommensen University Pematangsiantar is generally in the good to very good category. The aspects of teaching readiness, teaching materials, teaching discipline, and teaching evaluation received very good ratings. The aspect of lecturer personality was in the good category. However, we must improve lecturer performance in the aspect of research. We must improve productivity, continuity of research activities, and scientific publications. The results of this study are expected to be used as evaluation material and a basis for policy-making for institutions in their efforts to improve the quality of lecturers and higher education in a sustainable manner.